1985
DOI: 10.1007/bf00020641
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of plant protoplasts with DNA: cotransformation of non-selected calf thymus carrier DNA and meiotic segregation of transforming DNA sequences

Abstract: With the DNA transformation procedure developed in our laboratory (13) several transformed tobacco SR1 tissues were obtained which, apart from selected and non-selected pTi sequences (T(+)), also had acquired non-selected calf thymus carrier DNA sequences (C(+)), being integrated in their nuclear genomes. From one such tissue (cNT4), with a shooty crown gall phenotype and expressing mannopine synthesis activity (Mas(+)), shoots were grafted and mature, flowering plants (gNT4) were obtained. After cross pollina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…In the cotransformation of animal cells by the calcium phosphate-DNA coprecipitation method, both transforming DNAs often are ligated together in the cell before insertion into the chromosome (1,18). Similar results have been found in plant cells transformed by the calcium phosphate-DNA coprecipitation technique (2,17). Ira contrast to the rearranged DNA integrated following coprecipitation, T-DNA transferred to plant cells via Agrobacteriurn is usually a well defined piece of DNA delimited by the 25 base direct repeat T-DNA border sequences (7).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In the cotransformation of animal cells by the calcium phosphate-DNA coprecipitation method, both transforming DNAs often are ligated together in the cell before insertion into the chromosome (1,18). Similar results have been found in plant cells transformed by the calcium phosphate-DNA coprecipitation technique (2,17). Ira contrast to the rearranged DNA integrated following coprecipitation, T-DNA transferred to plant cells via Agrobacteriurn is usually a well defined piece of DNA delimited by the 25 base direct repeat T-DNA border sequences (7).…”
Section: Discussionsupporting
confidence: 61%
“…In coprecipitation methods, plant cells are typically exposed to the transforming D N A for 30 minutes (8,17), but in Agrobacteriummediated methods, plant cells are exposed to the bacteria for two to four days (11,22). Agrobacterium t r a n s f o r m a t i o n systems have a high probability of transferring one, intact copy of a foreign gene to plant cells, and this advantage should extend to the cotransfer of several independent genes.…”
Section: Discussionmentioning
confidence: 99%
“…In experiments using direct DNA transformation or Agrobacterium tumefaciens to transfer DNA to tobacco, a single genetic locus has been found in 18/20 cases (Otten et al 1981 ;Memelink et al 1983;Wostemeyer et al 1984;Paszkowski et al 1984;De Block et al 1984;Horsch et al 1984Horsch et al , 1985Sengupta-Gopalan etal. 1985;Hain et al 1985;Potrykus et al 1985;Deshayes et al 1985;Peerbolte et al 1985;de Framond et al 1986;Czako and Marton 1986). The explanation for the occurrence of multiple loci cannot therefore be found in differences of experimental organism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of Ti plasmid carrying a mutated vir region, confirmed that the vir region was not essential for transformation by direct DNA uptake. Such studies [44,68] also provided evidence for co-transformation, sequences characteristic of calf thymus DNA used as carrier being detected in transformed plants by Southern blot hybridisation. The transformation frequency in all these experiments with Ti plasmid was of the order of 1 in l0 4 to 10 5 [18,43].…”
Section: Agrobacterium Ti Plasmidmentioning
confidence: 90%